Making visible the pedagogical practices with a differential approach - Castaño Marín, Angela Patricia
This article refers to the research project “Pedagogical practices with a different approach for the SENA instructors”, which aimed to facilitate and strengthen comprehensive vocational training for apprentices with intellectual functional diversity, as a strategy for social and labor inclusion, adjusting to the “SENA Inclusive” policies. In this article, the concept of disCAPACITY is referenced from a vision that observes the POTENTIAL and not the lack of, framing it in the respect to the difference, under the concept of people with functional diversity; a strategy approved by the Trade and Services Center of SENA (SENNOVA), Regional Caldas.